KONSEP DIRI TERHADAP KENAKALAN REMAJA DALAM PERSPEKTIF FILSAFAT ILMU - Sefti Rholanjiba; Sudjarwo, sudjarwo; Muhammad Nurwahidin‬ (JOEL: Journal of Educational and Language Research, 2022)
Adolescence is a transition from a child to an adult human. A person's picture and design of himself as a whole, both physical skills, spiritual skills, interaction skills and academic skills. Adolescents who do not know self-concept and increase positive self-concept will appear deviant behavior such as juvenile delinquency. This study aims to determine the self-concept of juvenile delinquency in the perspective of the philosophy of science by using the Literature Review method. The literature sources were obtained from the OJS database indexed by the Ministry of Education and Culture's Sinta for the last 10 years. The results of this study, there is a relationship and influence of the conceptualized self on juvenile delinquency, that a self who has a positive concept must avoid himself into juvenile delinquency. The philosophical assumptions consisting of Ontology, Epistemology, and Axiology in this study are the six dimensions of psychological well-being, the factors of juvenile delinquency, and the role of counseling services in overcoming these problems.